Ankle edema after administration of selective serotonin reuptake inhibitors - Konstantinos Kontoangelos; Marina Ecomomou; Charalambos Papageorgiou (Mental Illness)
Clinical manifestations of drug-induced skin reactions include a wide range of symptoms, from mild drug-induced exanthemas to dangerous and life-threatening generalized systematic reactions. Druginduced skin reactions to psychotropic medication are usually associated with antiepileptic drugs. However, a significant role can be assigned to selective serotonin reuptake inhibitors. We report a case of a female patient, who after approximately one month therapy with escitalopram developed a bilateral ankle edema, which resolved completely within the first week following its discontinuation. Although serious complications are rare, clinicians should be aware of severe skin complications in patients treated with antidepressants, which necessitate careful clinical monitoring and management. Individualization of pharmacotherapy is crucial, together with regular evaluation of safety and tolerance of the treatment.